The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1007/s40279-023-01887-0
|View full text |Cite
|
Sign up to set email alerts
|

Building Bridges Instead of Putting Up Walls: Connecting the “Teams” to Improve Soccer Players’ Support

Abstract: The increase in the economic value of soccer occurred in parallel with an increase in competing demands. Therefore, clubs and federations evolved to greater specialization (e.g., state-of-the-art facilities and high-profile expertise staff) to support players’ performance and health. Currently, player preparation is far from exclusively club or national team centered, and the lack of control in each player’s environment can be more prevalent than expected. For example, an elite group of professional players fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 86 publications
(150 reference statements)
0
0
0
Order By: Relevance
“…Consequently, athletes can be surrounded by multidisciplinary support teams, including different coaches (technical, tactical, managing), physiotherapists, psychologists, and medical doctors. In this context, physical training and testing should therefore ideally play a supportive role and help frame the fundamental aspects of the training process rather than necessarily taking the center stage in the holistic performance optimization (162).…”
Section: The Role Of Formal Fitness Testing In Relation To Training/c...mentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, athletes can be surrounded by multidisciplinary support teams, including different coaches (technical, tactical, managing), physiotherapists, psychologists, and medical doctors. In this context, physical training and testing should therefore ideally play a supportive role and help frame the fundamental aspects of the training process rather than necessarily taking the center stage in the holistic performance optimization (162).…”
Section: The Role Of Formal Fitness Testing In Relation To Training/c...mentioning
confidence: 99%
“…Accordingly, a survey among sports science practitioners in high-level soccer reported that poor coach buy-in was a substantial barrier to the implementation of an effective player-monitoring program (423). In addition, the increase in expert staff associated with players, both within and outside clubs (with players increasingly hiring personal coaches), warrants transparency and sharing of information (162). Thus, clear communication, e.g., around test results and training directions, should be highly emphasized in relation to all relevant stakeholders.…”
Section: Athlete and Organization Awareness And Buy-inmentioning
confidence: 99%